Fanconi anemia mesenchymal stromal cells-derived glycerophospholipids skew hematopoietic stem cell differentiation through Toll-like receptor signaling - Amarachintha, Surya (Stem Cells, 2015)
Fanconi anemia (FA) patients develop bone marrow (BM) failure or leukemia. One standard care for these devastating complications is hematopoietic stem cell transplantation. We identified a group of mesenchymal stromal cells (MSCs)-derived metabolites, glycerophospholipids and their endogenous inhibitor, 5-(Tetradecyloxy)-2-furoic acid (TOFA), as regulators of donor hematopoietic stem and progenitor cells (HSPCs). We provided two pieces of evidence that TOFA could improve hematopoiesis-supporting function of FA MSCs: (1) limiting-dilution CAFC assay revealed that TOFA significantly increased cobblestone colonies in Fanca−/− or Fancd2−/− co-cultures compared to untreated co-cultures. (2) Competitive repopulating assay using output cells collected from co-cultures showed that TOFA greatly alleviated the abnormal expansion of the donor myeloid (CD45.2+Gr1+Mac1+) compartment in both peripheral blood and BM of recipient mice transplanted with cells from Fanca−/− or Fancd2−/− co-cultures. Further, mechanistic studies identified Tlr4 signaling as the responsible pathway mediating the effect of glycerophospholipids. Thus, targeting Glycerophospholipid biosynthesis in FA MSCs could be a therapeutic strategy to improve hematopoiesis and stem cell transplantation.